HUBUNGAN KEJADIAN KARIES GIGI DENGAN KUALITAS HIDUP ANAK - Eneng Susilawati; Yenni Hendriani Praptiwi; Denden Ridwan Chaerudin; Sri Mulyanti (Poltekkes Kemenkes Bandung, 2023)
Dental caries in children can interfere with the chewing process and result in reduced nutritional intake, resulting in suboptimal growth and development. The emersion of teeth caries impair the digest process and as the result it decreased dietary admission therefore it effect the childrens gowth and developmental. This study aimed to analyze the connection between dental caries and the quality of childrens life. This study was a cross sectional, the subject was 81 elementary students at SDIT Al Fatwa Bandung using simple random sampling method. Tests were accepted involving arbitrary inspecting technique upwards of 81 understudies. The results showed caries status in children obtained an average def-t value of 4.9, average DMF-T value obtained as much as 2.43, the average pufa value obtained as much as 4, and the average PUFA value obtained as much as 2. A total of 59 students have a moderate quality of life. Test analysis using the chi-square test showed a significant relationship between dental caries status and children's quality of life (p <0.05). It is hoped that special attention will be paid to children's dental health problems by visiting dental health services at least once every 6 months.